2020
DOI: 10.7717/peerj.9173
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram to predict overall survival and cancer-specific survival for patients with anaplastic thyroid carcinoma

Abstract: Background Anaplastic thyroid carcinoma (ATC) is a rare malignant tumor with a poor prognosis. However, there is no useful clinical prognostic predictive tool for ATC so far. Our study identified risk factors for survival of ATC and created a reliable nomogram to predict overall survival (OS) and cancer-specific survival (CSS) of patients with ATC. Methods A total of 1,404 cases of ATC diagnosed between 1983 and 2013 were extracted from on the Surveillance, Epidemiology and End Results database based on our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
8
5
0
Order By: Relevance
“…The survival rate of patients ≥ 65 years old was less than that of patients < 65 years old, confirming the findings of Gui et al. ( 12 ). Smallridge et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The survival rate of patients ≥ 65 years old was less than that of patients < 65 years old, confirming the findings of Gui et al. ( 12 ). Smallridge et al.…”
Section: Discussionsupporting
confidence: 89%
“…Age was a prognostic factor for CSS in patients with ATC. The survival rate of patients ≥ 65 years old was less than that of patients < 65 years old, confirming the findings of Gui et al (12). Smallridge et al (13) demonstrated that, for patients diagnosed with early ATC, surgical treatment, chemotherapy, radiotherapy, and systemic treatment can achieve optimal survival outcomes, while active palliative and clinical care are crucial for individuals with advanced ATC (14).…”
Section: Discussionsupporting
confidence: 62%
“…Age has been associated with thyroid cancer-speci c survival and is included in the AJCC staging system for patients with differentiated thyroid cancer [20]. In our study, being older than 65 years was a negative prognostic factor, which was consistent with the ndings of Gui and Wang et al [19,21]. The predictive value of tumor diameter was controversial in different studies [5,21,22], potentially due to the different cutoff values used in those studies.…”
Section: Discussionsupporting
confidence: 88%
“…However, to date, a convenient predictive model for predicting BM in RCC has not been developed, which means that the personal risk of BM cannot be accurately estimated by combining all independent risk factors for BM. Nomograms are an easyto-understand and multivariate visualization model to predict and quantify the incidence of a specific clinical outcome for individual patients and are widely applied in various malignancies [22][23][24]. Each independent risk factor included in the model was given a weighted point value to represent its effect on BM in RCC.…”
Section: Discussionmentioning
confidence: 99%